2004
DOI: 10.1557/proc-814-i8.5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Thin Films in Flexible Displays

Abstract: The use of brittle materials in flexible displays requires the understanding of the mechanical limitations of the materials and the various display architectures. We discuss various approaches to mechanical bend tests for components of flexible displays and describe a new test method based on a three-axis motion. We discuss the mechanical limitations of indium tin oxide (ITO) as a transparent conductor, and present results for a more mechanically robust multilayer transparent conductor made of an ITO-metal-ITO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The X-Y-θ method assumes a uniform bending deformation along the length of devices. In the testing process, [65] one end of the sample was fixed in a flat plate and the moving end was controlled by a rotary motorized actuators. As shown in Figure 7, the length between two ends is L 0 , and the initial horizontal direction is defined as X axis.…”
Section: X-y-θ Methodsmentioning
confidence: 99%
“…The X-Y-θ method assumes a uniform bending deformation along the length of devices. In the testing process, [65] one end of the sample was fixed in a flat plate and the moving end was controlled by a rotary motorized actuators. As shown in Figure 7, the length between two ends is L 0 , and the initial horizontal direction is defined as X axis.…”
Section: X-y-θ Methodsmentioning
confidence: 99%
“…The initial resistance of samples were measured and are comparable to theoretical value as in Table 1. The collapsing radius test method is adopted for our experiment because it offers simple setup and testing a function of radius [4]. Since the sample does not conform to a constant radius for the bended area and extracting the true minimum radius of curvature at the center point between the plate is not trivial [4,5], we use a new approach to simplify the radius measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The collapsing radius test method is adopted for our experiment because it offers simple setup and testing a function of radius [4]. Since the sample does not conform to a constant radius for the bended area and extracting the true minimum radius of curvature at the center point between the plate is not trivial [4,5], we use a new approach to simplify the radius measurement. By fitting an ellipse to the digital image of bended curve of the sample and measuring its two axis a and b, as shown in Figure 2, the radius of curvature can be calculated as R= b2/a.…”
Section: Methodsmentioning
confidence: 99%
“…Dealing with flexible displays, Grego et al [2] evaluated two measurement systems, each with different advantages in bending test capability: a collapsing radius system [3] and an X Y bending system [4]. In the collapsing radius set-up, the bending shape is, however, not exactly cylindrical and a numerical study [5] concluded that, assuming perfectly elastic behavior, the minimum bending radius experienced by the sample is 20% smaller than the half platedistance.…”
Section: Introductionmentioning
confidence: 99%